Enhancing Kindergarten Teachers' Implementation of Integrated Learning through an Interactive Online Platform: A Case Study in the UAE - Alzouebi, Khadeegha; Alkaabi, Maitha Obaid; Charles, Tendai (Journal of Ecohumanism, 2025)
This study explores the impact of an online website on enhancing kindergarten teachers' capabilities in implementing integrated learning in their classrooms. Integrated learning is crucial for fostering connections across various subjects, enabling students to create meaningful links between different domains. A mixed-methods approach was employed, combining quantitative data from a post-evaluation survey with qualitative insights. A prototype website was developed, providing resources across three main subjects—English, Mathematics, and Science—based on specific themes. The effectiveness of this website was evaluated through feedback from 17 kindergarten teachers in Al Ain, United Arab Emirates (UAE), using a survey distributed via email. Findings indicate that the website was successful in aiding teachers to implement integrated learning, with a significant majority reporting the utility of the resources in integrating subjects effectively. Teachers found the website easy to navigate and the materials relevant and applicable to classroom settings. Feedback also highlighted areas for improvement, including features for teacher contributions and continuous resource updates. The study confirms the potential of technology, particularly websites, in supporting integrated learning initiatives in early childhood education. This research underscores the importance of integrating technology into teaching strategies to enhance integrated learning. For policymakers and educators, the study suggests investing in digital platforms that offer accessible, relevant, and engaging educational resources. Future research should focus on expanding the website's functionalities and exploring its impact across a broader demographic.